Pemanfaatan Parafrase Berbasis Artificial Intelligence Sebagai Salah Satu Teknologi Digital Untuk Meningkatkan Efisiensi Penyelesaian Tugas Mahasiswa di Surabaya - Reza Putri Angga; Kanessa Jasmine; Sharleen Agustine; Muhammad Aryasatya; Natalia Desy Anggraini (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2024)
Utilization of Artificial Intelligence-Based Paraphrasing Improves Efficiency of Student Assignment Completion in Surabaya. In this era of over-evolving technology, artificial intelligence technology (AI) has made significant contributions in various fields, including education. One potential implemantation of artificial intelligence technology is an automated AI-based online paraphrasing tool in education 4.0 era. This research aims to examine the effectiveness of using AI-based online paraphrasing in improving the efficiency of student assigntment completion in Surabaya. The research metodolgy involved a survey with student from various universities in Surabaya with a descriptive approach technique. The results show that the use of AI-based online paraphrasing tools can significantlu reduce the time needed to complete assignments without reducing the quality of the content. This tools helps students to understand the material, develop writing skills, and avoid plagiarism. This research result is expected to encourage the use of digital technology in the learning process, which is expected to improve academic productivity. Thus, AI-based online paraphrasing tools can be part of a more modern and effective learning strategy.